Identification of sterile a-motif domain-containing 9-like as a potential biomarker in patients with cutaneous melanoma - Ye,Junsen; Tang,Haidan; Xie,Chuanrui; Han,Wei; Shen,Guoliang; Qian,Ying; Xu,Jin (PeerJ, 2023)
Skin cutaneous melanoma (SKCM) is one of the most aggressive malignancies, accounting for approximately 75% of skin cancer-related fatalities annually. Sterile a-motif domain-containing 9-like (SAMD9L) has been found to regulate cell proliferation and suppress the neoplastic phenotype, but its specific role in SKCM remains unknown. To investigate the cancer-associated immunology of SKCM and the role of SAMD9L in tumor progression, we conducted an integrative bioinformatics analysis that revealed elevated expression levels of SAMD9L in SKCM. ROC curves and survival analyses confirmed the considerable diagnostic and prognostic abilities of SAMD9L. Moreover, a real-world cohort of 35 SKCM patients from the First Affiliated Hospital of Soochow University showed that higher expression levels of SAMD9L were associated with better prognosis. We performed validation experiments, including cell culture, generation of lentiviral-transfected SKCM cell lines, cell proliferation assay, and transwell assay, which demonstrated that down-regulation of SAMD9L significantly promoted proliferation and migration capacities of SKCM cells. Additionally, SAMD9L expression was found to be strongly linked to immune infiltration. Our results revealed a positive correlation between SAMD9L and XAF1 expression, suggesting that SAMD9L may serve as a prospective prognostic indicator of SKCM with co-expressed XAF1 gene. In summary, our findings indicate that SAMD9L may serve as a promising prognostic and therapeutic biomarker and play a critical role in tumor-immune interactions in SKCM.
Keywords: SAMD9L; Melanoma; Immune; Prognosis